Synthesis, Characterization and Antifungal Studies of Metal Complexes of Benzoyl-and Salicylhydrazones of N-Methylacetoacetanilide - Deepa, K.P.; Aravindakshan, K.K.; Suhara, F. (Asian Journal of Chemistry, 2010)
Complexes of Mn(II) Co(II), Ni(II), Cu(II), Zn(II), Cd(II) and Hg(II) with benzoylhydtazone, L1H2 and salicylylhydrazone, L 2H3 of N-methylacetoacetanilide have been prepared and characterized. The IR spectral studies indicate that the ligands act either as bidendate donors coordinating through aroyl oxygen and azomethine nitrogen atoms or as tridentate donors coordinating through aroyl- and anilide oxygen and azomethine nitrogen atoms. Antifungal studies of Mn(II), Co(II), Ni(II) and Cu(II) complexes with four selected fungal strains were also carried out.